Use of organic manure and fertilizer in rice (Oryza sativa) wheat (Triticum aestivum) cropping system for sustainability - Kumar, Alok; Yadav, D S (The Indian Journal of Agricultural Sciences, 2012)
A long-term field experiment was initiated in 1984 on a sodic soil (pH 8.8 and exchangeablesodium 27%) to study the effect of organic manures, fertilizers and their integrated use inrice (Oryza sativa L.)-wheat (Triticum aestivum L. emend. Fiori & Paol.) cropping system.During initial years (1984-87) 25- 50% substitution of fertilizers through organic sources(farmyard manure, green-manure and wheat straw) reduced the rice yield by 6-23% comparedwith 100% fertilizers alone. In the following years, 25-50% N through farmyard manure orprickly sesban (Sesbania aculeta (Retz.) Pers.; syn S. cannabina Pers. var cannabina Baker]green-manure along with 50-75% fertilizers to rice gave either equal or more yield comparedwith 100% NPK fertilizers (120 kg N/ha, 26.2 kg P/ha, 33.2 kg K/ha) alone. Farmyard manureand green-manure of prickly sesban were found superior to wheat straw for grain yield andNPK uptake. The organic source with fertilizers decreased the soil pH, electricalconductivity and exchangeable sodium (%) at faster rate and depleted micronutrient cations(Cu, Mn, Zn, Fe) at slower rate than inorganic fertilizers alone.